Methane emissions from oil and gas production on the North Slope of Alaska. (1st December 2019) - Floerchinger, Cody; McKain, Kathryn; Bonin, Timothy; Peischl, Jeff; Biraud, Sébastien C.; Miller, Charles; Ryerson, Thomas B.; Wofsy, Steven C.; Sweeney, Colm
Abstract: Recent warming of the Arctic has motivated assessments of methane (CH4 ) release from the North Slope Region of Alaska (NSRA). This study examines the contributions of thermogenic emissions from the Prudhoe Bay Oil Field (PBOF) to the elevated concentrations of atmospheric CH4 observed across the NSRA. We report high precision atmospheric measurements of CH4 and ethane (C2 H6 ) within and downwind of the PBOF. Biogenic CH4 emissions, due to methanogenic processes within the Arctic tundra, are not co-emitted with C2 H6 . We show that the thermogenic gas emanating from oil and gas extraction point sources contains on average 1 mol of C2 H6 for every 16 mol of CH4 . We use a mass balance approach to estimate total emissions of thermogenic CH4 from two days in the summer of 2016 and find 2–5 times greater emissions than the sum of all sources in the PBOF reported to the EPA Greenhouse Gas Reporting Program in 2016. Although higher than reported, these emissions are much smaller than estimates of CH4 emissions from other oil and natural gas production areas in the US, and they make a very small contribution to total CH4 emissions from the North Slope. Highlights: Aircraft measurements provide new insight into natural gas emissions in the Arctic. CH4 Loss from Prudhoe Bay Oil Field is 2–5 times higher than inventory estimates. Natural gas emissions from Prudhoe Bay are small compared to other petroleum fields. No evidence for Thermogenic CH4 emissions in the Arctic outside of Prudhoe Bay.